Character Design of Mahapatih Gajah Mada Based on Visual References from Bima and Brajanata/Kertala Statues - Setia Budi, Hutomo; Adnyana, I Wayan; Swandi, I Wayan; Suardina, I Nyoman (VCD, 2023)
Mahapatih Gajah Mada was a great figure who united the archipelago in his time, but no statues have been found that depict the figure. Archaeologists disagree on the accuracy of the human head statue artifact referenced by Mr. Muhammad Yamin, as it does not have any markers that indicate it is a statue of Mahapatih Gajah Mada. To design an accurate visualization of the character design of Mahapatih Gajah Mada, this design is divided into 2 stages: data mining and character design. Data mining involves a data search related to Mahapatih Gajah Mada and culture during the Majapahit Kingdom Era. Character design involves designing the character design of Gajah Mada using data from the references that have been obtained. Data searches have revealed that Mahapatih Gajah Mada is likely to be the Brajanata/ Kertala character in the Panji story and the Bima character in the Mahabarata story. The character has a large, tall body, strapping, crossed mustache, and wavy curls, using a headdress in the form of a foreheadband with carvings, upper arm bands made with snake motifs, a belt with a Kala head patterned buckle, and an upawita (caste rope) that crosses from the left shoulder to the right waist depicting Gajah Mada's caste. For weapons, Gajah Mada carries a keris with a cundrik type (not notched) and an oval mace, which means that Gajah Mada is one of Lord Vishnu's attendants who has a guardian nature. The design of the oval mace takes reference from door guard statues. Keywords: Character Design, Gajah Mada, Majapahit kingdom